Numerical solution of base shear in high tensioned cable antenna - Seyed Amirodin Sadrnejad (Numerical Methods in Civil Engineering)
A finite element solution based on equevalent elements is proposed for the static and dynamic analysis of tallhigh tensioned cable antennas. To reduce high number of degrees of freedom in space frame body of a structure, a simple equivalent beam element is defined for each simulative substructure. This numerical procedure is applicable to analyze complex three dimensional assemblies of substructures of such similar complex structures. In this analysis wind pressure effects accompanied by change of postentioning loads in nonlinear cable elements, earthquake effects, and any other arbitrary loads on the substructures. Accordingly, the restriction of the loads on the cable elements to gravity and thermal loads can be applied. The algorithm is developed upon an efficient cable elements depending on the given position and curved geometry of the cable, its end forces, and its tangent stiffness matrix. The employed formulation scheme permits any magnitude of deformation for straight or curved elements. The postensioning stresses in cables were considered as initial stresses. To simulate the equevalent elements, both ends stiffness, damping and mass components are calibrated to present the same static and dynamic responses as the selected substructure. To simulate dynamic responses, the equevalent single mass matrix and its adjusted position are carried out to obtain the same frequencies in equevalent elements. The static solution of a complete structure compared well with the results presented by simulated model. This paper proposes an alternative structural analysis modeling strategy for guyed steel towers design, considering all the equivalent structural forces and moments, by using three-dimensional beam finite elements. Comparisons of the above mentioned design models with an alternative, that models the main structure and the bracing system with 3D beam finite elements, are made for existing guyed steel telecommunication towers (325m high). The comparisons are initially based on the towers static and dynamic structural behavior later to be followed by a linear buckling analysis to determine the influence of the various modeling strategies on the tower stability behaviour.